Use of portable vitrectomy instrumentation (VISC X) in the rural Guatemalan highlands. Issue 9 (September 1982) - Kingham, J D; Poirier, R H; Annel, M; Erickson, D
Abstract : In a rural mountain setting 20 patients with blinding ocular opacities were treated surgically with modern vitrectomy techniques. There were no intraoperative or postoperative complications unique to the isolated environment. Because of its compact portability, the VISC X proved to be an ideal vitrectomy instrument. In addition to plastic lid procedures, cataract extraction, and strabismus surgery, repair of retinal detachment and vitrectomy in selected cases has been added to the armamentarium of surgeons who are seriously involved in exporting ophthalmology to remote places.